Criminological insights: A comprehensive spatial analysis of crime hot spots of property offenses in Malaysia's urban centers - Azizul Ahmad; Tarmiji Masron; Syahrul Nizam Junaini; Mohamad Hardyman Barawi; Mohd Sofian Redzuan; Yoshinari Kimura; Norita Anak Jubit; Luqman Haqim Bismelah; Asykal Syakinah Mohd Ali (ResearchGate, 2024)
This study examines property crime trends in Selangor, Kuala Lumpur, and Putrajaya from 2015 to 2020, utilizing Geographic Information Systems (GIS) and comprehensive crime data from the Royal Malaysia Police. It focuses on the relationship between property crime rates and the delineation of police station jurisdictions across Selangor State, Kuala Lumpur Federal Territory (KLFT), and Putrajaya Federal Territory (PFT). The objective is to understand the dynamics of property crime, its evolution, and the influence of the National Transformation Program on crime prevention strategies. By assessing the spatial distribution of property crimes, this research aims to identify underlying trends and the efficacy of hot spot policing. The analysis is underpinned by an extensive review of secondary data from the Intelligence/Operations/Records Division of the Royal Malaysia Police Headquarters, enabling a deep dive into the spatial characteristics of property crime within these regions. The findings contribute to the broader understanding of crime prevention in Malaysia, underscoring the importance of GIS technology and the need for strategic interventions tailored to specific crime patterns. This study provides critical insights for policymakers and law enforcement to formulate evidence-based strategies, enhance public safety, and inform future crime prevention efforts.